Death Hurts, But It Isn't Fatal: The Postexit Diffusion of Knowledge Created by Innovative Companies - Hoetker, Glenn; Agarwal, Rajshree (Academy of Management Journal, 2007)
There is little understanding of whether a firm's innovative knowledge dies with it or if instead significant diffusion of knowledge occurs even after a firm exits an industry. Theoretical predictions about the differing effects of firm exit on private and public knowledge and implications for interfirm knowledge transfer are forwarded. We investigated main and moderating effects of a firm's exit from the disk drive industry on knowledge diffusion to other firms, finding evidence that the ability to use a firm as a template plays a critical role in successfully replicating its knowledge. Absent this template, knowledge “stickiness” reduces knowledge diffusion.